2019
DOI: 10.1111/age.12836
|View full text |Cite
|
Sign up to set email alerts
|

Genomic clues of the evolutionary history of Bos indicus cattle

Abstract: SummaryTogether with their sister subspecies Bos taurus, zebu cattle (Bos indicus) have contributed to important socioeconomic changes that have shaped modern civilizations. Zebu cattle were domesticated in the Indus Valley 8000 years before present (YBP). From the domestication site, they expanded to Africa, East Asia, southwestern Asia and Europe between 4000 and 1300 YBP, intercrossing with B. taurus to form clinal variations of zebu ancestry across the landmass of Afro‐Eurasia. In the past 150 years, zebu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 87 publications
2
45
1
2
Order By: Relevance
“…For diversity analysis, the existing number of samples in each breed greater than 12 was adequate and in consonance with other studies (Upadhyay et al, 2017;Colli et al, 2018). It has also been indicated that sample size as small as 4 -6 (Willing et al, 2012) and polymorphic SNP filtration (Colli et al, 2018;Utsunomiya et al, 2019) can mitigate ascertainment bias as long as the number of markers is sufficiently large as those under the current investigation. Earlier, in Indian dairy cattle breeds, we also tested bovine high-density genotyping array to assess its feasibility for Zebu cattle genomic studies (Dash et al, 2018).…”
Section: Roh Distribution and Genomic Inbreedingsupporting
confidence: 81%
“…For diversity analysis, the existing number of samples in each breed greater than 12 was adequate and in consonance with other studies (Upadhyay et al, 2017;Colli et al, 2018). It has also been indicated that sample size as small as 4 -6 (Willing et al, 2012) and polymorphic SNP filtration (Colli et al, 2018;Utsunomiya et al, 2019) can mitigate ascertainment bias as long as the number of markers is sufficiently large as those under the current investigation. Earlier, in Indian dairy cattle breeds, we also tested bovine high-density genotyping array to assess its feasibility for Zebu cattle genomic studies (Dash et al, 2018).…”
Section: Roh Distribution and Genomic Inbreedingsupporting
confidence: 81%
“…in the 50k SNP chip discovery panel, recorded the highest p-values (S2 Table), confirming that the strategy implemented here removed those SNPs having the largest ascertainment bias impact. Importantly, the H o values of the reference breeds obtained using our SNP selection approach were comparable with those of the Illumina BovineHD array, which is still today considered the most robust SNP array for cattle [24,42]. Further, the population structure analyses performed using the reduced dataset provided results in line with the know relationship among the reference populations in our dataset, whereas the same analysis performed using the full SNP was distorted by the percentage of taurine ancestry in a given breed (S6 Fig).…”
Section: Plos Onementioning
confidence: 57%
“…About the same number of zebus lives in the tropical regions (Utsunomiya et al . 2019). Both taurine cattle and zebu descend from the extinct aurochs.…”
Section: The Bovine Speciesmentioning
confidence: 99%
“…A more detailed account of the domestication of zebu has been presented by Utsunomiya et al . (2019).…”
Section: Domestication Dispersal and Differentiation Of Breedsmentioning
confidence: 99%
See 1 more Smart Citation